Determinants of Energy Intake from Ultra-Processed Food Consumption among Adolescent Girls in Tasikmalaya City, Indonesia - Lilik Hidayanti; Dian Saraswati; Rizka Fikrinnisa (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2026)
Adolescence is a critical period characterized by significant physical, cognitive, psychosocial, and emotional changes that influence dietary behaviors, including increased consumption of ultra-processed foods (UPFs), which may contribute to chronic disease risk. This study aimed to analyze the determinants of energy intake from UPFs among adolescent girls in Tasikmalaya City. This observational study employed a cross-sectional design, involving 514 adolescent girls from 10 public junior high schools in Tasikmalaya, selected through proportional random sampling. The energy intake from UPFs was collected using 2×24-hour food recalls, then separated using Nova 4. Information on potential determinants, including individual and interpersonal factors, was obtained through a structured questionnaire. Data were analyzed using the chi-square test and logistic regression. The results showed that one-fifth (21%) of participants had energy intake dominated by UPFs. Significant individual factors associated with the dominance of energy intake from UPFs included screen time duration (p = 0.001; OR = 2.424 [95% CI = 1.420-4.140]) and main meals (p = 0.019; OR = 1.996 [95% CI = 1.121-3.554]). Interpersonal factors related to the dominance of energy intake from UPFs were family status (p = 0.006; OR = 2.336 [95% CI = 1.275-4.282]). Screen time duration emerged as the strongest contributing factor. In conclusion, dominant energy intake from UPFs among adolescent girls is influenced by screen time duration, main meals, and family status. Parents need to pay attention to adolescent girls’ nutritional intake, especially limiting UPFs consumption. Policies regarding healthy snacks sold in school cafeterias also need to be implemented.